Radônio como indicador de contaminação no solo por NAPLs - Sarah Andresa Bonfim (2018)
Contamination of soils and groundwater is cause of concern all over the world. Such contamination is mainly due to the production, poor storage and handling of fuels, in places such as gas stations and military installations. Thus, the knowledge and development of analytical techniques of contamination by NAPLs (Non-Aqueous Phase Liquids) is important, these analysis methodologies tend to contribute to the remediation of contaminated soils and aquifers, reducing the difficulties of measurement, costs and enhancing the evaluation of degraded areas as a tool for decision-making. Using radon as a natural tracer for identifying areas contaminated by NAPLs is a technique that arises and develops within its potential to contribute to remediation plans. The technique has emerged due to radon show strong affinity for organic substances and, therefore, the NAPLs. Areas contaminated with NAPLs have radon concentrations significantly lower than areas that are not contaminated, due to the partitioning of radon between soil gases, water and NAPLs. In this work it was observed that the radon partition coefficient between distinct types of NAPL and water is high, showing this affinity for the organic substances, fact also proven by the Hildebrand solubility parameter. In an area known to be contaminated by diesel, several measurements were made, using radon gas as a natural indicator of soil contamination. For the measurements, the AlphaGUARD® PQ 2000 PRO detector was used, a radon monitor of great international prestige. The results showed that, at the contamination site, the radon concentration observed in the soil gases is strongly lower than the concentration of the uncontaminated area of the same region. The results showed the effectiveness of the use of radon as the natural tracer of contamination and the methodology used